Die mensbeeld in die skeppingsverhale van Genesis - Olivier, Johannes Petrus Jacobus (Journal for semitics, 1989)
An analysis is given of the meanings of the two expressions characterizing man's function in the creation narratives, viz subdue (kb) the earth and have dominion (rdh) over the animals. Since kb also seems to convey the meaning of ""to prepare (the land)"" or ""to cultivate (the fields)"" and rdh embodies the meaning of ""shepherding (the flocks)"", it can be argued that these two expressions reflect the two basic modes of existence in Ancient Israel, namely that of the pastoralist on the one hand, and that of the agriculturalist on the other. This is probably the type of scenario that one would expect reading the creation narratives. The origin of the image of man is not to be found in or to be identified with ancient royal ideology, but rather with that of the ancient farmers and shepherds of Palestine.